Pollination efficiency of important insect visitors on pomegranate (Punica granatum) under mid hill conditions of Himachal Pradesh - THAKUR, SAKSHAM; THAKUR, RAJ KUMAR; SHARMA, HARISH KUMAR; KUMAR, PRAMOD; THAKUR, RIMPIKA; SHANDIL, DEEPIKA (The Indian Journal of Agricultural Sciences, 2024)
Insect pollinators are found to be highly significant in enhancing the quality fruit production and productivity. The experiment was conducted during April–May 2020 and 2021 at Dr Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to determine the pollination indices of significant insect pollinators visiting pomegranate (Punica granatum L.). The data on pooled basis from two years revealed that Bombus haemorrhoidalis visited most number of flowers during the day (4.96 flowers/min) followed by Apis mellifera (4.24), Apis cerana (3.95), Apis dorsata (3.76) and Episyrphus balteatus (3.09). The time spent on each flower was maximum by A. cerana (17.10 sec/flower) followed by E. balteatus (17.04 sec), A. dorsata (14.20 sec), A. mellifera (13.07 sec) and haemorrhoidalis (5.36 sec) irrespective of different day hours. A. mellifera (5.43 bees/m2/2 min) activity was maximum followed by A. cerana (5.06), E. balteatus (2.91 visitors/m2/2 min), B. haemorrhoidalis (1.72) and A. dorsata (1.37). Data on loose pollen grains for the two years revealed that A. dorsata adhered maximum number of loose pollen grains (357.00 thousand) followed by B. haemorrhoidalis (283.00 thousand), A. mellifera (98.00 thousand), cerana (41.00 thousand) and solitary bees (28.00 thousand). A. mellifera scored highest pollination index and A. dorsata scored least pollination index. A. mellifera, A. cerana and B. haemorrhoidalis are the primary pollinators that increase pomegranate pollination efficiency whereas A. dorsata, E. baltaeatus and solitary bees are supplementary insects improving pollination in various crops including pomegranate. A. mellifera, A. cerana, B. haemorrhoidalis and A. dorsata were main foragers of pomegranate flowers ensuring effective and efficient pollination.